Reducing asthma attacks in children using exhaled nitric oxide (RAACENO) as a biomarker to inform treatment strategy: a multicentre, parallel, randomised, controlled, phase 3 trial. Issue 6 (June 2022) - Turner, Steve; Cotton, Seonaidh; Wood, Jessica; Bell, Victoria; Raja, Edwin-Amalraj; Scott, Neil W; Morgan, Heather; Lawrie, Louisa; Emele, David; Kennedy, Charlotte; Scotland, Graham; Fielding, Shona; et al.
Summary: Background: The benefit of fractional exhaled nitric oxide (FeNO) in guiding asthma treatment is uncertain. We evaluated the efficacy of adding FeNO to symptom-guided treatment in children with asthma versus only symptom-guided treatment. Methods: RAACENO was a multicentre, parallel, randomised, controlled, phase 3 trial done in 35 secondary care centres and 17 primary care recruitment sites (only seven primary care sites managed to recruit patients) in the UK. Patients with a confirmed asthma diagnosis, aged 6–15 years, prescribed inhaled corticosteroids, and who received a course of oral corticosteroids for at least one asthma exacerbation during the 12 months before recruitment were included. Participants were randomly assigned to either FeNO plus symptom-guided treatment (intervention) or symptom-guided treatment alone (standard care) using a 24 h in-house, web-based randomisation system. Participants and the clinical and research teams were not masked to the group allocation. A web-based algorithm gave treatment recommendations based on the Asthma Control Test (ACT) or Childhood ACT (CACT) score; current asthma treatment; adherence to study treatment in the past 3 months; and use of FeNO (in the intervention group). Follow-up occurred at 3-month intervals for 12 months. The primary outcome was any asthma exacerbation treated with oral corticosteroids in the 12 months after randomisation, assessed in the intention-to-treat population. This study is registered with the International Standard Randomised Controlled Trial Registry, ISRCTN67875351. Findings: Between June 22, 2017, and Aug 8, 2019, 535 children were assessed for eligibility, 20 were ineligible and six were excluded post-randomisation. 509 children were recruited and at baseline, the mean age of participants was 10·1 years (SD 2·6), and 308 (60·5%) were male. The median FeNO was 21 ppb (IQR 10–48), mean predicted FEV1 was 89·6% (SD 18·0), and median daily dose of inhaled corticosteroids was 400 μg budesonide equivalent (IQR 400–1000). Asthma was partly or fully controlled in 256 (50·3%) of 509 participants. The primary outcome, which was available for 506 (99%) of 509 participants, occurred in 123 (48·2%) of 255 participants in the intervention group and 129 (51·4%) of 251 in the standard care group, the intention-to-treat adjusted odds ratio (OR) was 0·88 (95% CI 0·61 to 1·27; p=0·49). The adjusted difference in the percentage of participants who received the intervention in whom the primary outcome occurred compared with those who received standard care was −3·1% (−11·9% to 5·6%). In 377 (21·3%) of 1771 assessments, the algorithm recommendation was not followed. Adverse events were reported by 27 (5·3%) of 509 participants (15 in the standard care group and 12 in the intervention group). The most common adverse event was itch after skin prick testing (reported by eight participants in each group). Interpretation: We found that the addition of FeNO to symptom-guided asthma treatment did not lead to reduced exacerbations among children prone to asthma exacerbation. Asthma symptoms remain the only tool for guiding treatment decisions. Funding: National Institute for Health Research.